The mediating effect of dynamic capabilities on the relationship between customer relationship management and innovation capability - Araújo, Cíntia Cristina Silva de (2017)
A fundamental factor to achieve competitive advantage is the ability to foresee market tendencies faster and more efficiently than competitors. Organizations can adapt themselves to this ever changing environment by building solid customer relationships that enable them to anticipate market trends and customer demands. In this scenario, Customer Relationship Management (CRM) is an important organizational initiative to acquire customer knowledge, to develop individualized marketing strategies and to customize products and services according to marked needs. In turn, dynamic capabilities are fundamental for organizations to rearrange and renew their resources as to respond to environmental changes. Finally, innovation capability is a capacity that organizations should develop in order to translate all knowledge attained from the environment into innovative and profitable initiatives. Literature shows that CRM can provide valuable customer knowledge that helps organizations rearranging their resources and processes to create innovative solutions and services that meet market demands. For this reason, this research aims to answer the following question: what is the effect of CRM and dynamic capabilities on the development of innovation capability in organizations? To answer this question, the main goal of this research is to identify the relationship between CRM, dynamic capabilities and innovation capability. One of the main contributions of this study is to show, for the first time, that for itself CRM cannot bring innovation capability. For organizations to develop innovation capability they need to combine CRM with dynamic capabilities; as they are able to rearrange their resources and process, organizations can develop innovation capability. Another contribution of this research is the development a new instrument to measure CRM, dynamic capabilities and innovation capability.